2016
DOI: 10.5812/ircmj.39870
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotic Yogurt on Constipation in Pregnant Women: A Randomized Controlled Clinical Trial

Abstract: BackgroundProbiotics can alter the colonic microbiota and might improve bowel function.ObjectivesThe aim of this study was to evaluate the effect of the consumption of yogurt, enriched with Bifidobacterium and Lactobacillus 4.8 × 1010 (CFU) on the symptoms of constipated pregnant women.Materials and MethodsThis triple-blind randomized controlled trial was conducted on 60 constipated pregnant women who were diagnosed by the ROME III criteria in Tabriz, Iran from December 2014 to July 2015. Participants were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 29 publications
3
55
0
1
Order By: Relevance
“…The third study did not provide a between‐group statistical analysis; however, the decrease in constipation frequency score was approximately twofold greater in the probiotic groups than in the placebo group . Four studies reported no significant effect of 4 different probiotic treatments; however, 1 of these studies showed a nonsignificant trend in favour of probiotics . Of the 7 studies, 5 had been published since the original consensus.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The third study did not provide a between‐group statistical analysis; however, the decrease in constipation frequency score was approximately twofold greater in the probiotic groups than in the placebo group . Four studies reported no significant effect of 4 different probiotic treatments; however, 1 of these studies showed a nonsignificant trend in favour of probiotics . Of the 7 studies, 5 had been published since the original consensus.…”
Section: Resultsmentioning
confidence: 99%
“…After applying inclusion and exclusion criteria, 33 RCTs that reported on the effects of probiotics in the management of lower GI symptoms in clinical practice published since January 2012 were identified, and considered in conjunction with 37 RCTs included in the original systematic review. Of the 33, 6 publications were found in the June 2017 update . These could not be included in the consensus voting process; however, they were reviewed by the Steering Committee, which decided that the new evidence provided in these studies would not alter the results of the Delphi consensus and so could be included in our publication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations